Acetate metabolism does not reflect astrocytic activity, contributes directly to GABA synthesis, and is increased by silent information regulator 1 activation. Issue 6 (23rd January 2017) - Rowlands, Benjamin D.; Klugmann, Matthias; Rae, Caroline D.
Abstract : Acetate is a poor substrate for energy generation and it also, at high concentrations (> 2 mmol/L), inhibits metabolism of glucose and of itself. Potassium depolarisation results in decreased use of acetate and decreased incorporation of acetate into glutamine showing that acetate metabolism does not necessarily reflect astrocytic activity. GABA is not only made via astrocytic glutamine, but acetate is converted as well directly to GABA in neurons. Acetate metabolism is likely regulated via acetylation of the metabolizing enzyme acetyl‐CoA synthetase. Changes in acetate metabolism should be interpreted as modulation of metabolism through changes in cellular energetic status via altered enzyme acetylation levels rather than simply as a glial–neuronal adjustment of metabolic activity. Abstract: [ 13 C]Acetate is known to label metabolites preferentially in astrocytes rather than neurons and it has consequently been used as a marker for astrocytic activity. Recent discoveries suggest that control of acetate metabolism and its contributions to the synthesis of metabolites in brain is not as simple as first thought. Here, using a Guinea pig brain cortical tissue slice model metabolizing [1‐ 13 C]D‐glucose and [1, 2‐ 13 C]acetate, we investigated control of acetate metabolism and the degree to which it reflects astrocytic activity. Using a range of [1, 2‐ 13 C]acetate concentrations, we found that acetate is a poor substrate for metabolism and will inhibit metabolism of itself and of glucose at concentrations in excess of 2 mmol/L. By activating astrocytes using potassium depolarization, we found that use of [1, 2‐ 13 C]acetate to synthesize glutamine decreases significantly under these conditions showing that acetate metabolism does not necessarily reflect astrocytic activity. By blocking synthesis of glutamine using methionine sulfoximine, we found that significant amount of [1, 2‐ 13 C]acetate are still incorporated into GABA and its metabolic precursors in neurons, with around 30% of the GABA synthesized from [1, 2‐ 13 C]acetate likely to be made directly in neurons rather than from glutamine supplied by astrocytes. Finally, to test whether activity of the acetate metabolizing enzyme acetyl‐CoA synthetase is under acetylation control in the brain, we incubated slices with the AceCS1 deacetylase silent information regulator 1 (SIRT1) activator SRT 1720 and showed consequential increased incorporation of [1, 2‐ 13 C]acetate into metabolites. Taken together, these data show that acetate metabolism is not directly nor exclusively related to astrocytic metabolic activity, that use of acetate is related to enzyme acetylation and that acetate is directly metabolized to a significant degree in GABAergic neurons. Changes in acetate metabolism should be interpreted as modulation of metabolism through changes in cellular energetic status via altered enzyme acetylation levels rather than simply as an adjustment of glial–neuronal metabolic activity.